FACTORS INFLUENCING THE ADOPTION OF THE E-LEARNING TECHNOLOGY IN TEACHING AND LEARNING BY STUDENTS OF A UNIVERSITY CLASS - Barhoumi Chokri (European Scientific Journal, ESJ, 2012)
﻿The main objective of this study is to provide students and actors of online education in a university with solutions for influencing factors of students’ positive opinion about the use of the e-learning technology in teaching and learning. This paper is meant to improve the use of instructional technology in our region for societal benefit and the technological learning development. We believe that it is impossible to improve innovations in increasing sustainable applications of technology in education without answering the question: Why aren't students interested in e-learning? What are the learning technological factors that may influence the positive opinion about the use of e-learning technology for teaching and learning? The result of the experimentation shows clearly that 78.8% of the surveyed students have a high experience in general use of Internet services and they are familiar with Internet technology. Result shows also that only 23.2% of them state that they have a high experience in using Internet for learning. The survey results also show that 59.6% of students have problems in using ICTs for learning (Information and communication technologies for learning). The survey results show that 44.4% and 19.2% respectively disagree and strongly disagree with the statement that the learning process is based on cognitive flexibility.